Fergana food and oil snot expansion and problems in production processes - Amonov Yahya Akbarjon Ogli (Zien Journals, 2024)
The article presents the history of the reform of state ownership of cocoon industry enterprises in Fergana in the 1918s, their unification into syndicates, and the liquidation of enterprises based on small-scale production. The technical shortcomings of production activities in the cocoon industry, the food industry, problems and issues related to the implementation of established five-year plans are highlighted. Issues such as the use of workers' wages to compensate for technical errors in cocooning industrial enterprises and the introduction of fines for low income are described
Keywords: cocoon; food; enterprises; cartels